ВОЛНА Р300 В РЕШЕНИИ НЕЙРОКОГНИТИВНЫХ, СОЦИАЛЬНЫХ ЗАДАЧ И В ИССЛЕДОВАНИЯХ ИСКУССТВЕННОГО ИНТЕЛЛЕКТА - Лытаев, Сергей Александрович; Суровицкая, Юлия Владимировна; Новгородцева, Ксения Александровна (FORCIPE, 2022)